2019
DOI: 10.1590/0034-7167-2018-0352
|View full text |Cite
|
Sign up to set email alerts
|

Digital technologies for promotion of healthy eating habits in teenagers

Abstract: Objective: Identify and analyze the scientific literature on digital technologies for promotion of healthy eating habits in teenagers. Method: Integrative review of articles published in English and Spanish, available in full on four databases. The descriptors used were (Adolescent health) OR (Teen health) AND (Healthy diet) OR (Healthy eating) AND (Educational technology) OR (Instructional technology), respectively, from which eight articles were selected. Results: Among the studies included, three were dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
16

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 30 publications
0
16
0
16
Order By: Relevance
“…Several studies have also confirmed the association between the use of social media and health-related risk factors and behaviours among young people, such as anxiety and depression, sexual behaviours, and substance misuse (Gebremeskel et al, 2014;Ilakkuvan et al, 2018;Keles et al, 2020;Steers et al, 2016). However, some previous studies have also argued that social media can be a vital tool in healthy lifestyle promotion (Alcântara et al, 2019;Laranjo et al, 2015). Therefore, there is still a need for more empirical studies, particularly from more diverse contexts, in order to have a broader understanding of the effects of social media on youth health (Richards et al, 2015).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Several studies have also confirmed the association between the use of social media and health-related risk factors and behaviours among young people, such as anxiety and depression, sexual behaviours, and substance misuse (Gebremeskel et al, 2014;Ilakkuvan et al, 2018;Keles et al, 2020;Steers et al, 2016). However, some previous studies have also argued that social media can be a vital tool in healthy lifestyle promotion (Alcântara et al, 2019;Laranjo et al, 2015). Therefore, there is still a need for more empirical studies, particularly from more diverse contexts, in order to have a broader understanding of the effects of social media on youth health (Richards et al, 2015).…”
Section: Introductionmentioning
confidence: 93%
“…Previous studies have also shown that youth unhealthy behaviours and practices could be tackled through social media-based interventions (Hsu et al, 2018;Ramo et al, 2018). For instance, there is evidence confirming the effectiveness of the use of digital technologies for promoting healthy eating habits, mental health and physical activity among young people (Alcântara et al, 2019;Laranjo et al, 2015). In this sense, youth and health workers, and policymakers from Mauritius can further explore the use of social media in designing effective and preventive youth health interventions.…”
Section: Implications and Limitationsmentioning
confidence: 99%
“…19 Programlarda hemşireler tarafından sıklıkla tercih edilen öğretim yöntemleri düz anlatım, vaka sunumu, resimli veriler, koçluk, yüz-yüze/ telefonla görüşme, yüz-yüze/ telefonla danışmanlık, motivasyonel görüşme, sağlık mesajları, kısa mesajlar, grup çalışması, okul dışında küçük grup oturumları, sağlık istasyonları, kukla oyunu, çizgi filmler, video gösterimi, dijital oyunlar, web sitesi ve internet programlarıdır. 6,11,16,[17][18][19][20][21][22][23][24][25][26][27][28] Ancak areket kaslarını çalıştıran motor oyunlara daha az rastlanmaktadır. 23,29 Oysaki motor oyunlar, teorik bilginin kalıcılığını sağlayarak davranış değişikliğini teşvik etmektedir.…”
Section: Introductionunclassified
“…Known as the digital generation, adolescents yearn for new techniques and technologies for the health area, especially when it comes to digital education, to serve as a differential in gaining their attention, as it demonstrates preference for new technologies when compared to a traditional strategy aimed at education and health promotion. 7 Knowledge promotion needs to happen in an attractive and efficient manner, which is possible when using educational games as a tool in health education for adolescents. Educational games can be considered tools that are fun, but are also capable of facilitating and assisting learning, and can facilitate behavioral changes by promoting a rearrangement of educational contingencies.…”
Section: Introductionmentioning
confidence: 99%